Vegetation response to soil salinity and waterlogging in three saltmarsh hydrosequences through macronutrients distribution. (5th January 2018) - Ferronato, Chiara; Speranza, Maria; Ferroni, Lucia; Buscaroli, Alessandro; Vianello, Gilmo; Vittori Antisari, Livia
Abstract: Saltmarshes consist of soil hydrosequences, where the complex interactions between water tide fluctuations, soil physicochemical properties and plant colonization contribute to the triggering of the pedogenetic processes and consequently to the stability of the saltmarsh edges. In this study, the composition and richness of the vegetation cover were investigated along soil transects in three different saltmarshes. With the aim to investigate the response of the vegetation to the soil hydroperiod and its influence on the availability of soil nutrients, plant and soil samples were collected in four representative sites on each saltmarsh transect (hydrosequence). Among the different species of saltmarshes, L. vulgare and S. europaea colonized intertidal areas, where an accumulation of nutrients (Ca, K, P, S and Na) and organic C and total N (OC and TN, respectively) was found. These intertidal areas are the "critical transition zones", which drive the transition between the terrestrial and the aquatic systems along the increase of soil salinity and water saturation. Among the different element cycles analysed in the soil-plant system, the analysis of the Na and S dynamic, through both bioconcentration and translocation indexes, explains the different adaptation mechanisms to different salinity and waterlogging stressors. The limiting of the species areal was generally associated firstly with a decrease in their Na and S bioconcentration factor and, to a lesser extent, with the increase in their Na and S translocation. Graphical abstract: